FINANCIAL EXPERTS ON THE BOARD: DOES IT MATTER FOR THE PROFITABILITY AND RISK OF THE U.K. BANKING INDUSTRY?. (25th March 2019) - Apergis, Nicholas
Abstract: In this article, I explore the relation among board‐level financial expertise, profitability, and risk with panel data from the U.K. banking industry. The empirical findings document that collectively, financial experts have a positive influence on the performance of banks; contribute to higher risks, especially for large banks; and improve the stock performance of banks. Moreover, the results highlight that board‐level qualified accountants have no statistical effect on profitability, whereas financial and banking professors, as well as financial experts from other industries, have a positive effect. Such findings imply that these two groups of professional financial experts may more easily adopt group‐level profit enhancements. Robustness checks confirm the results for all types of banking institutions, except those with strong real estate portfolios. Finally, certain commercial and/or policy implications of the results are reported.